Echoes of scripture in the letters of Paul - Hays, Richard B. (Yale Univ. Pr., 1989)
Paul's letters, the earliest writings in the New Testament, are filled with allusions, images and quotations from the Old Testament. This book investigates Paul's appropriation of Scripture from a perspective based on recent literary-critical studies of intertextuality.